Profil Kadar Asetil Kolinesterase Pada Petani Pengguna Pestisida Di Kabupaten Jeneponto - Muawanah wana; Andi Fatmawati; Nur Qadri Rasyid; Anita; Dita Pramudya (LPPM POLBITRADA, 2025)
Pesticides are chemicals used to control pest or overcome problems in plants due to pests or plant-disturbing organisms. One indicator to determine the impact of pesticide poisoning on humans is the examination of acetyl cholinesterase. If there is a decrease in the activity of this enzyme, it can cause nervous system disorders, namely symptomps of acute pesticide poisoning such as headaches, nausea, vomiting, skin irritation and even blindness. The purpose of this study was to determine the profile of acetyl cholinesterase levels in farmers using pesticides in Jeneponto Regency. The method used is the butyrylthiocholine method with a sample size of 15 samples. The results of the examination of 15 samples obtained were 1 sample had a decreased acetyl cholinesterase level of 1,749 µ / L compared to the normal reference value of 4,620 - 11,500 µ / L. while the other 14 samples obtained cholinesterase levels with normal values. It can be concluded that the profile of acetyl cholinesterase levels of farmers using pesticides with an age range of 20 years and over and a work period of > 3 years is still in the normal category.